What do we mean by "system"? – System Beliefs and Worldviews in the INCOSE Community. Issue 1 (16th August 2018) - Sillitto, Hillary; Griego, Regina; Arnold, Eileen; Dori, Dov; Martin, James; McKinney, Dorothy; Godfrey, Patrick; Krob, Daniel; Jackson, Scott
Abstract: The System Definition Survey issued to INCOSE Fellows in December 2016 revealed at least five radically distinct worldviews on Systems within a relatively small, but moderately representative, part of the INCOSE community. We describe and analyse the survey results, and comment on differences between the responses from the Fellows and the responses to a similar survey issued to the System Science Working Group a month later. Then we discuss how the different worldviews on "system" revealed by the surveys map onto different areas of the set of system definitions described in a previous paper. We conclude that all the worldviews identified offer useful perspectives for systems engineering, and that Systems Engineers need the flexibility to adopt different worldviews for different situations, or at least to act "as if" different worldviews are true in different situations.